2020
DOI: 10.1007/s12298-020-00871-6
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variability of panicle architecture in indigenous rice landraces of Koraput region of Eastern Ghats of India for crop improvement

Abstract: Panicle architecture is an important character that influence reproductive success and contributes directly to grain yield. In the present study, we evaluated diversity of panicle traits in 77 indigenous rice landraces from Koraput and compared with three popularity cultivated hybrid varieties of the locality for possibility of using in crop improvement program. Significant morphological variations of panicle traits such as panicle number, panicle angle, panicle weight, panicle length, grain number and grain w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 31 publications
1
9
0
Order By: Relevance
“…It suggested that these parameters are the major determinant for phenotypic diversity in studied genotypes compared to other traits. Similar results of phenotypic diversity of morpho-physiological traits are also proclaimed in traditional rice landraces (Panda et al 2020c) and in underutilized millets (Panda et al 2020b) from Koraput. Based on panicle attributes, genotypic relationship among the studied nger millet genotypes were evaluated by cluster analysis (Fig.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…It suggested that these parameters are the major determinant for phenotypic diversity in studied genotypes compared to other traits. Similar results of phenotypic diversity of morpho-physiological traits are also proclaimed in traditional rice landraces (Panda et al 2020c) and in underutilized millets (Panda et al 2020b) from Koraput. Based on panicle attributes, genotypic relationship among the studied nger millet genotypes were evaluated by cluster analysis (Fig.…”
Section: Discussionsupporting
confidence: 70%
“…Kumari and Singh (2016) reported that yield of nger millet relies upon different growth and yield characteristics like lled grain number, panicle number and grain weight. In contrast, it was also reported that variation of grain yield was not necessarily associated with leaf area in cereals like nger millet (Panda et al 2020b) and rice (Subrahmanium 2000;Panda et al 2020c).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the traits studied, the NOSPP and the NFGPP exhibited maximum phenotypic and genotypic coefficient of variation, thus ensuring their significance in utilization for grain yield improvement breeding programs [ 36 , 37 ]. The magnitude of the difference between GCV and PCV shows the amount of environmental influence on these traits, and the low difference refers to the occurrence of strong genetic effects [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Genetic advance coupled with high heritability is a more reliable measure for determining the usefulness of selection on the traits. Related to our study, high h 2 and GASM combination was observed for the major traits, viz., PH, NFGPP, NOPB, NOSB, TGW, and GYP [ 37 , 41 , 42 ], and thereby allowed for selection in segregating generations in conventional recombination breeding methods.…”
Section: Discussionmentioning
confidence: 99%